Reward Board Design to Stimulate Early Childhood Worship Behavior - Susanti, Yeni; Fajriah, Heliati; Muthmainnah, Muthmainnah (Universitas Pahlawan Tuanku Tambusai, 2025)
The learning media used to stimulate worship behavior in early childhood is very minimal based on the analysis of the need that this media is very important and based on market analysis is still relatively rare so it needs to be developed. This research uses a Research and Development (RD) approach with the ADDIE (Analisys, Design, Development, Implementation, Evaluation) model. The research sample amounted to 20 children aged 5-6 years. Data collection techniques include media expert validation and material expert validation as well as direct observation of children's involvement in using reward board media. The results of the study showed that the reward board was very feasible to use, with a media expert score of 92% and a material expert score of 100%. The results of the child's response test showed results ranging from 80% to 94.29%. This study shows that reward board media can effectively stimulate early childhood worship behavior.